Social Cognition in Rehabilitation Context: Different Evolution of Affective and Cognitive Theory of Mind in Mild Cognitive Impairment - Federica Rossetto; Francesca Baglio; Davide Massaro; Margherita Alberoni; Raffaello Nemni; Antonella Marchetti; Ilaria Castelli (Behavioural Neurology)
Maintaining social skills such as Theory of Mind (ToM) competences is important to counteract the conversion into dementia in Mild Cognitive Impairment (MCI). Multidimensional nonpharmacological interventions demonstrated their potential in improving cognitive and behavioral abilities; however, little is known about the long-term effect of such interventions on social skills in people with MCI. The aim of this longitudinal study was to monitor ToM competences considering both cognitive and affective domains in an amnestic MCI (aMCI) sample involved in a home-based multistimulation treatment (MST@H). 30 aMCI subjects (M:F=15:15; mean age±SD=77.00±4.60) were enrolled, and three steps of evaluation with neuropsychological tests and ToM tasks have been implemented. 21 healthy controls (HC) were also included (M:F=9:12; mean age±SD=74.95±3.88) to characterize the aMCI sample regarding differences in ToM performance compared to HC at the baseline evaluation. Our results show that the aMCI group statistically significantly underperformed the HC group only in the advanced ToM tasks, confirming an initial decline of high-level ToM competences in this population. The longitudinal evaluation revealed time changes not only in some subcognitive domains of MoCA (memory and executive functions) but also in cognitive and affective ToM dimensions in aMCI subjects. Our findings suggest that cognitive and affective ToM can be considered useful outcome measures to test the long-term effect of treatment over time.